Naringin mitigates testicular injury and associated neuronal toxicity in lead-exposed cockerel chicks - Oluwaseun Esan; Chinomso Ebirim; Moses Olusola Adetona; Temitayo Ajibade; Ademola Adetokunbo Oyagbemi; Temidayo Omobowale; Omolade Abodunrin Oladele; Adeolu Adedapo; Momoh Yakubu; Evaristus Nwulia; Oluwafemi Oguntibeju (Mashhad University of Medical Sciences, 2024)
Objective: Lead (Pb) poisoning affects multiple organs including the reproductive system. The experiment was performed to explore the protective effect of naringin on testicular apoptosis, neuronal dysfunction and markers of stress in cockerel chicks.Materials and Methods: Thirty-six cockerel chicks were used for this study, and randomly grouped into six chicks per group viz. control, Pb only (600 ppm), Pb and naringin (80 mg/kg), Pb and Naringin (160 mg/kg), naringin only (80 mg/kg) and naringin only (160 mg/kg), respectively, for eight weeks. Pb was administered via drinking water while naringin was administered via oral gavage. Oxidative stress indices in the brain and testes were assessed, and immunohistochemistry of TNF-α and caspase 3 was done in the brain and testes, respectively.Results: Lead administration induced inflammatory and testicular apoptosis cascade accompanied with increased oxidative stress and upregulation of brain and testicular antioxidant enzymes in comparison to the control and Pb-only-treated cockerels. Immunohistochemistry showed significant immunoreactivity of testicular caspase 3 and TNF-α in the brain.Conclusion: Treatment of Pb-exposed chickens with naringin offered protection to Pb acetate-induced testicular oxidative stress, apoptosis, and neuroinflammation in cockerel chicks.